2019
DOI: 10.1186/s12906-019-2558-9
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial characteristics of Berberine against prosthetic joint infection-related Staphylococcus aureus of different multi-locus sequence types

Abstract: Background Staphylococcal aureus (S. aureus) has become the leading causative pathogen of Prosthetic Joint Infection (PJI), which is the most devastating complication after arthroplasty surgeries. Due to the biofilm formation ability and emergence of multiple-drugs resistance strains of S. aureus , it has become an urgency to find new anti-staphylococcal agents to establish effective prophylaxis and treatment strategy for PJI. Extracted from a traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 71 publications
4
31
0
Order By: Relevance
“…To maximize the relevance of our research to clinical situations, the clinical isolates covered almost all types of clinical infections, including samples from nasal colonization, superficial skin and soft tissue infection, and blood infection (Table S1). BBR showed poor antibacterial activity against S. aureus with MIC 90 at 512 ug/mL, which is consistent with previous studies and should be attributed to the thick cell wall of the pathogen and the rigid structure of berberine alkaloids [18,19]. Therefore, the combined use of compounds that increase membrane permeability (such as SNH) with BBR may increase the amount of the latter into bacterial cells and promote antibacterial activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To maximize the relevance of our research to clinical situations, the clinical isolates covered almost all types of clinical infections, including samples from nasal colonization, superficial skin and soft tissue infection, and blood infection (Table S1). BBR showed poor antibacterial activity against S. aureus with MIC 90 at 512 ug/mL, which is consistent with previous studies and should be attributed to the thick cell wall of the pathogen and the rigid structure of berberine alkaloids [18,19]. Therefore, the combined use of compounds that increase membrane permeability (such as SNH) with BBR may increase the amount of the latter into bacterial cells and promote antibacterial activity.…”
Section: Discussionsupporting
confidence: 89%
“…Cortex and Coptis chinensis Franch and fully chemically synthesized now [14], has been widely used to treat bacterial diarrhea and gastroenteritis for many years in China [15,16]. Several studies have demonstrated the antibacterial activities of berberine alone or as a synergist of antibiotics [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Our research revealed that the MIC of berberine against C. difficile strains ranged from 256 to 1.024 mg/L. In contrast, Tan et al showed that the MIC values of berberine varied from 64 to 512 mg/L against Staphylococcus aureus [31]. Wang et al found that the MIC value of berberine for C. difficile spores was 640 mg/L [17].…”
Section: Discussionmentioning
confidence: 62%
“…Most importantly, it has been reported for antiviral activity against numerous viruses such as influenza virus (Wu et al, 2011), enterovirus 71 (Wang et al, 2017), human cytomegalovirus (Hayashi et al, 2007), hepatitis C virus (Hung et al, 2019), HSV-1 (Dkhil & Al-Quraishy, 2014) and chikungunya virus (Varghese et al, 2016). Besides, it has been proven to be an antibacterial agent against multiple drug resistance bacteria such as methicillin-resistant Staphylococcus aureus and Streptococcus agalactiae (Chu et al, 2016;Peng et al, 2015;Tan et al, 2019;Yu et al, 2005) and antifungal agent against Candida spp. (Xie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%